Sources of the sages: developing a systematic method for the identification of Jewish-Christian intertextuality in the Babylonian Talmud - Brand, Christiaan Burger (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.